2012
DOI: 10.1056/nejmoa1109071
|View full text |Cite
|
Sign up to set email alerts
|

Placebo-Controlled Trial of Tofacitinib Monotherapy in Rheumatoid Arthritis

Abstract: BackgroundTofacitinib (CP-690,550) is a novel oral Janus kinase inhibitor that is being investigated as a targeted immunomodulator and disease-modifying therapy for rheumatoid arthritis. MethodsIn this phase 3, double-blind, placebo-controlled, parallel-group, 6-month study, 611 patients were randomly assigned, in a 4:4:1:1 ratio, to 5 mg of tofacitinib twice daily, 10 mg of tofacitinib twice daily, placebo for 3 months followed by 5 mg of tofacitinib twice daily, or placebo for 3 months followed by 10 mg of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
567
1
37

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 882 publications
(658 citation statements)
references
References 15 publications
27
567
1
37
Order By: Relevance
“…meaningfully between the two tofacitinib treatment armsmost likely reflecting the overlapping pharmacokinetic exposures within the dose range studied. The high event frequencies of PTLD and serious infections reported in the fixed-dose tofacitinib treatment groups in this Phase 2b transplant study were contrary to the findings in patients with rheumatoid arthritis (3)(4)(5)(6)(7)(8), which is likely attributable to differences in patient populations and the more intense and complex combination immunosuppressive regimens received by transplant patients.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…meaningfully between the two tofacitinib treatment armsmost likely reflecting the overlapping pharmacokinetic exposures within the dose range studied. The high event frequencies of PTLD and serious infections reported in the fixed-dose tofacitinib treatment groups in this Phase 2b transplant study were contrary to the findings in patients with rheumatoid arthritis (3)(4)(5)(6)(7)(8), which is likely attributable to differences in patient populations and the more intense and complex combination immunosuppressive regimens received by transplant patients.…”
Section: Discussioncontrasting
confidence: 98%
“…Cytokine signaling through the JAK pathway is integral to lymphocyte activation, proliferation and function; thus, inhibition of JAK3 and/or JAK1 results in suppression of multiple aspects of the immune response (1,2). The efficacy of tofacitinib for the treatment of moderate to severe rheumatoid arthritis has been demonstrated in many studies (3)(4)(5)(6)(7)(8). Tofacitinib is also being developed for the treatment of other autoimmune disorders such as psoriasis (9) and inflammatory bowel disease (10).…”
Section: Introductionmentioning
confidence: 99%
“…Six phase III RCTs have demonstrated significant improvements in signs and symptoms of active RA compared with placebo (17)(18)(19)(20)(21) or MTX (22). PROs have been reported from all 6 phase III trials, and they have demonstrated significant improvements with tofacitinib treatment versus placebo, with and without background MTX, across a range of patient populations (23)(24)(25)(26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%
“…12 In the ORAL Solo trial, in patients with an inadequate response to DMARDs (most frequently methotrexate but including other nonbiological DMARDS, TNF inhibitors and other biological agents), the three-month ACR20 response rate with tofacitinib monotherapy (5mg twice daily) was 60% (vs 27% with placebo; p<0.001); this improvement was maintained after six months. 6 There was a corresponding reduction in disability score but disease activity was not significantly different from placebo at three months.…”
mentioning
confidence: 89%